Pengembangan Media Pembelajaran Interaktif Berbasis Mind Mapping pada Era Pembelajaran Jarak Jauh - Pratama, Devangga Putra Adhitya; Sakti, Norida Canda; Listiadi, Agung (Jurnal Pendidikan Ekonomi Undiksha, 2022)
The limited use of learning media in the era of distance learning makes schools need to optimize each material with alternative developments to evaluate self-evaluation, formula calculation schemes, and curve evaluation forms. The emergence of the offline version of desktop economic mind mapping media development in the era of distance learning has the following objectives: 1) to prioritize mind mapping-based interactive learning media; 2) to analyze the structure of practicality; 3) to analyze how significant the changes in student learning outcomes were before and before being given the media that had been developed; 4) to analyze the analysis related to assessing the responses, reactions, and perceived impacts after the use of developer media. The testing phase is limited to 20 students in class X IPS 1 and X IPS 2 at SMA Muhammadiyah 3 Surabaya. Researchers in collecting data using documentation methods, interviews, review sheets and expert validation, and questionnaires. The adoption of 4D stages (define, design, develop, dessiminate) is the method used to develop the product in this study with an application output in .EXE format (file extension) that is suitable for use on a Windows computer system. The results of the study refer to the development of the media which is stated to be very feasible with the percentage of material testing 93%, media testing 87%, evaluation testing 84%. The media level is stated to be very practical with a percentage of 90%. The effectiveness of the media shows an increase in understanding that is significantly more dominant than the results of measurements with other media. 88% positive responses were given by students to this development media. So that mind mapping-based interactive learning media can support students' understanding and be applied in the era of distance learning.